Perancangan Sistem Informasi Penjualan Air Galon Isi Ulang Di Kota Palangka Raya Berbasis Web - Wahyudi, Teguh; Sahay, Abertun Sagit; Sylviana, Felicia (Universitas Palangka Raya, 2022)
This system was built with the aim of being a medium of sales information for refilling gallon water depots and providing information for people who want to buy refill gallon water. With this system, it is expected to be useful as a medium for expanding information about refill gallon water depots, helping consumers to purchase gallons of refill water easily, and the purchase of refill gallon water can be done without the need for the charging depot location. The methodology used in the manufacture of